2022
DOI: 10.1186/s12935-022-02806-5
|View full text |Cite
|
Sign up to set email alerts
|

Natural essential oils as a new therapeutic tool in colorectal cancer

Abstract: Colorectal cancer (CRC) is the third most revalent type of cancer in the world and the second most common cause of cancer death (about 1 million per year). Historically, natural compounds and their structural analogues have contributed to the development of new drugs useful in the treatment of various diseases, including cancer. Essential oils are natural odorous products made up of a complex mixture of low molecular weight compounds with recognized biological and pharmacological properties investigated also f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 168 publications
0
10
0
Order By: Relevance
“…The cell inflammation induction by lipopolysaccharide (LPS) triggers a series of signaling pathways including MAPK and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) ( Li et al, 2016 ; Capó et al, 2021 ; Pezzani et al, 2023 ). MAPKs are involved in the phosphorylation of JNK, ERK and p38 which regulate the expression of MSK 1/2 and then p65 ( Xie et al, 2019 ; Garzoli et al, 2022 ; Li et al, 2023 ). Inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) are also key enzymes involved in inflammation and cell stress, being NO an important regulator of COX-2 expression and activity ( Sharifi-Rad et al, 2022c ; Li et al, 2023 ).…”
Section: Anticancer Mechanisms and Targeting Signaling Pathways By Al...mentioning
confidence: 99%
“…The cell inflammation induction by lipopolysaccharide (LPS) triggers a series of signaling pathways including MAPK and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) ( Li et al, 2016 ; Capó et al, 2021 ; Pezzani et al, 2023 ). MAPKs are involved in the phosphorylation of JNK, ERK and p38 which regulate the expression of MSK 1/2 and then p65 ( Xie et al, 2019 ; Garzoli et al, 2022 ; Li et al, 2023 ). Inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) are also key enzymes involved in inflammation and cell stress, being NO an important regulator of COX-2 expression and activity ( Sharifi-Rad et al, 2022c ; Li et al, 2023 ).…”
Section: Anticancer Mechanisms and Targeting Signaling Pathways By Al...mentioning
confidence: 99%
“…Digestive cancers represent a group of malignancies that arise from the gastrointestinal tract, with colorectal cancer (CRC) being one of the most prevalent and deadly forms (GBD 2019 Colorectal Cancer Collaborators, 2022; Zlatian et al, 2015); early detection and intervention are paramount as liver or CRC, when identified at a localized stage, has a significantly higher survival rate compared to advanced stages where the disease has metastasized to distant organs (Garzoli et al, 2022). A recent study was designed to explore the effect of β‐sitosterol on enhancing the killing activity of costimulatory cells against gastric cancer.…”
Section: Anticancer Effects and Mechanisms Of β‐Sitosterolmentioning
confidence: 99%
“…Cancer is a large group of diseases that vary in mode of onset, growth rate, diagnosis, detectability, invasive potential, metastasis, response to treatment and prognosis [122][123][124][125][126]. Numerous studies have also revealed that additional Paeonia constituents may be used to treat breast, lung, and liver cancers and leukaemia.…”
Section: Anticancer and Cytotoxic Propertiesmentioning
confidence: 99%